2014
DOI: 10.1002/eji.201344039
|View full text |Cite
|
Sign up to set email alerts
|

MyD88 signalling in myeloid cells is sufficient to prevent chronic mycobacterial infection

Abstract: Tuberculosis is a chronic infectious disease caused by Mycobacterium tuberculosis that is responsible for almost 1.5 million deaths per year. Sensing of mycobacteria by the host's immune system relies on different families of receptors present on innate immune cells. Amongst them, several members of the TLR family are involved in the activation of immune cells by mycobacteria, yet the in vivo contribution of individual TLRs to the protective immune response remains controversial. On the contrary, MyD88, the ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 79 publications
(93 reference statements)
1
19
0
Order By: Relevance
“…These genes have been demonstrated to be important regulators in inflammation and infection by modulating differentiation of hematopoietic progenitor cells or activation of immune cells as well as chemokine and cytokine production. Myd88 is a key component of cytokine production in the Toll-like receptor and IL1b signaling pathway [12]. Granulocyte/macrophage colonystimulating factor (GM-CSF) which is encoded by the CSF2 gene regulates macrophages activation in the process of MTB infection [13].…”
Section: Introductionmentioning
confidence: 99%
“…These genes have been demonstrated to be important regulators in inflammation and infection by modulating differentiation of hematopoietic progenitor cells or activation of immune cells as well as chemokine and cytokine production. Myd88 is a key component of cytokine production in the Toll-like receptor and IL1b signaling pathway [12]. Granulocyte/macrophage colonystimulating factor (GM-CSF) which is encoded by the CSF2 gene regulates macrophages activation in the process of MTB infection [13].…”
Section: Introductionmentioning
confidence: 99%
“…In order to study the specific role of MyD88 in the epithelium as well as DCs and macrophages, we used the MyD ON mouse model for Cre-mediated activation of functional MyD88. We and others have shown that this model allows the precise study of direct consequences of cell type-specific TLR-mediated signaling on the immune response [27,30,[36][37][38][39]. This gain-offunction model enabled us, as demonstrated previously, to restrict functional MyD88 signaling to the intestinal epithelium or CD11c + MNPs, encompassing both DCs and macrophages in intestinal tissues, while all other cells and tissues of the body remain deficient for MyD88 [30].…”
Section: Discussionmentioning
confidence: 66%
“…Indeed, MyD88 is critical for dendritic cell's potential to induce the differentiation of naive T cells into effector T cells producing IFN- γ , while reactivation of MyD88 signaling in CD11c or lysozyme M-expressing myeloid cells during Mycobacterium bovis infection is sufficient to restore systemic and local inflammatory cytokine production and to control pathogen burden. TNF- α and IFN- γ are particularly important in promoting the formation and function of the granulomas, whereas IL-10 is one of the main negative regulators of the response in both sarcoidosis and TB [7, 15, 29]. …”
Section: Discussionmentioning
confidence: 99%